Studi Timbulan Dan Komposisi Sampah Domestik Wilayah Pengembangan IV Kota Pekanbaru - Aris, Aris; Yenie, Elvi; Darmayanti, Lita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Sampling is carried out based on SNI 19-3964-1994. The results showed that the number of solid waste generated in units of weight in the District of Tenayan Raya was 0,431 kg/person/day and in the unit volume was 3,376 l/person/day. Waste generation in Bukit Raya Sub-district is in weight units of 0.483 kg /person/ day and in volume units of 3,376 l/person/day. The composition of domestic waste in Development Region IV is dominated by 54.5% food waste, 11.2% foliage, 6.9% plastic, 5.5% paper, 5.7% textile, 4.2% rubber, 3.4% glass and 3.3% metal.  Keywords: waste generation, composition of waste